Accelerating Refractive Rendering of Transparent Objects - Hui, K. C.; Lee, A. H. C.; Lai, Y. H. (Computer graphics forum, 2007)
In this paper, a technique is proposed for the rendering of transparent objects interactively using the method of refractive rendering. In the proposed technique, the refractive rendering algorithm is performed in two stages, namely the pre‐computation stage and the shading stage. In the pre‐computation stage, ray‐traced information, including directions and positions of rays, are generated by a ray tracing process and are stored in a set of ray lists. In the shading stage, these data are retrieved from the ray lists for computing the shading of an object. Using the proposed technique, photorealistic image of transparent objects and gemstones with various cuttings, material properties, lighting and background can be rendered interactively. By combining the refractive rendering technique with conventional shading techniques, jewelry and crystal designs can be rendered at a much higher speed comparing with conventional ray tracing techniques.